"Facies Analysis Applied To Quarrying" A review of the possible use of sedimentology to increase knowledge and use of ornamental sandstones. (2017) - Rossi, Francesco Giuseppe; Madonna, Sergio; Milli, Salvatore
Abstract: Quarrying is an important economic activity but has several impacts on environment. Some of these impacts can be mitigated or compensated during the activity but the main goal to obtain better results would be digging less material and augmenting the marketable percentage over the amount extracted. Facies analysis could be a useful tool to ameliorate an overall knowledge on sedimentary stone materials, helping improving marketability and reducing the volumes of waste material. This is particularly true on sandstones, usually used as ornamental stones because of their peculiarity in colour, geometry and fossils. Here we present an example of facies studies on the Manciano Sandstone of the Gamberaio quarry in Tuscany (Italy), in order to valorize its commercial varieties.